MODIFIED RAW MATERIALS: SYNTHESIS, CHARACTERIZATION AND APPLICATION FOR Cd²⁺ IONS REMOVAL - SEILKHANOVA, Gulziya A.; IMANGALIYEVA, Ainur N.; AKBAYEVA, Dina N.; KENZHALINA, Zhanna ZH. (Studia Universitatis Babeș-Bolyai Chemia, 2017)
The adsorption behavior of some low-cost adsorbents such as bentonite, meal thistle and carbonized walnut husk with respect to Cd2+ ions in aqueous solutions has been studied. The several process parameters (contact time, initial metal concentration, sorption capacity, extraction degree, rate constants, sorption rates and sorption energy) were found. For the Cd2+ ions adsorption the equilibrium time onto bentonite, meal thistle and carbonized walnut husk were found to be 2 h, 25 and 10 min, respectively. Adsorption parameters were determined using both Langmuir and Freundlich isotherms. Sorption isotherms of cadmium ions onto MBT (modified bentonite) and MTM (modified thistle meal) were the best of all described by the equation of Freundlich sorption (correlation coefficients are closest to unit). In contrast the sorption of Cd2+ ions onto MCWH (modified carbonized walnut husk) was described by the Langmuir isothermic model where the adsorption occurs on homogeneous surface by monolayer sorption without interaction between sorbed ions. The obtained results demonstrate that bentonite, meal thistle and carbonized walnut husk can remove Cd2+ ions from aqueous solutions. It means that cheap and available raw materials can be efficient adsorbents and capable to remove cationic heavy metal species from waste water. The ion-exchange mechanism of adsorption of cadmium ions by the MBT, MTM, MCWH was proposed.